Od pragnienia wolności do zdrady. Ewolucja motywu pasterki we wczesnych utworach Mickiewicza = From the desire for freedom to betrayal. Evolution of the Shepherd`s Motif in Mickiewicz`s Early Works - Narolska, Aneta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the research was to determine the transformations of the shepherdess motif in A. Mickiewicz`s early works. The series Ballady i romanse and the second and fourth parts of the drama Forefathers` Eve were analysed. The works are discussed in the context of the Spanish shepherd`s novel and the episode inserted in the novel Don Quixote by M. de Cervantes Saavedra. On the basis of the research, a conclusion was formulated about the inspiring role of Cervantes` work in Mickiewicz`s early works. It was also established that the evolution of the shepherdessmotif in the poet?sworkstook place as a result of the development of hisworkconsisting in enriching it with new romantic themes.
Keywords: Mickiewicz, Adam (1798-1855); Mickiewicz, Adam (1798-1855). Dziady; Mickiewicz, Adam (1798-1855). Ballady i romanse; Cervantes, Saavedra Miguel de (1547-1616); Cervantes, Saavedra Miguel de (1547-1616). Don Kochot; Cervantes, Saavedra Miguel de (1547-1616). Galatea; pasterka; Cervantes, Saavedra Miguel de (1547-1616). Don Quixote; Mickiewicz, Adam (1798-1855). Ballades and romances; Mickiewicz, Adam (1798-1855). Forefathers` Eve; shepherdess